The utilisation of test-taking strategies among female students in a tertiary institution - Asiah Jamil,; Mohd Sallehhudin Abd. Aziz,; Norizan Abdul Razak, (Penerbit UKM, 2010)
This article reports a study on test-taking strategies utilized by low and high proficiency female participants in an open-ended reading comprehension test. Based on purposive sampling, 10 students were selected from one tertiary institution. The study seeks to explore the test-taking strategies employed by female students of two levels of proficiency. Verbal reports from these participants were obtained via the retrospective protocol and playback sessions. The data provided information on participants’ thinking process and revealed how they arrived at their answers and the reasons for their choice of answers. The data were transcribed verbatim and analyzed qualitatively whereby patterns of strategies were identified and categorized. On the whole the results showed both levels employed almost the same total number of strategies, 24 and 22 for the high and low proficiency participants respectively. The conclusions were drawn upon the results of the data provided by limited number of participants and thus thrust aside the claim of representativeness in terms of test-taking strategy studies. However, the study allows a peek on the types of test-taking strategies utilized by students in the study which may also be employed by students in general.